Trajectories of depressive symptoms and risk of cardiovascular disease, cancer and mortality: a prospective cohort study - Han Chen; Xiaohe Wang; Zhi Cao; Chenjie Xu; Jiahao Min (General Psychiatry)
Background Depressive symptoms are established risk factors for various health outcomes. However, previous studies assessed depressive symptoms at a single time point, neglecting individual variations over time.Aims To identify depressive symptoms trajectories through repeated measures and examine their associations with cardiovascular disease (CVD), cancer and mortality.Methods This study included 20 634 UK Biobank participants free of CVD and cancer at baseline with two or more assessments of depressive symptoms during 2006–2016. Group-based trajectory modelling identified depressive symptoms trajectories. Incident CVD, cancer and mortality were followed up until 2021 through linked registries.Results Six depressive symptoms trajectories were identified: no symptoms (n=6407), mild-stable (n=11 539), moderate-stable (n=2183), severe-decreasing (n=206), moderate-increasing (n=177) and severe-stable (n=122). During a median follow-up of 5.5 years, 1471 CVD cases, 1275 cancer cases and 503 deaths were documented. Compared with the no symptoms trajectory, the mild-stable, moderate-stable and severe-stable trajectories exhibited higher CVD risk, with hazard ratios (HRs) (95% CIs) of 1.19 (1.06 to 1.34), 1.32 (1.08 to 1.34) and 2.99 (1.85 to 4.84), respectively. Moderate-increasing and severe-stable trajectories were associated with higher mortality risks, with HRs (95% CIs) of 2.27 (1.04 to 4.93) and 3.26 (1.55 to 6.88), respectively. However, the severe-decreasing trajectory was not associated with higher risks of adverse outcomes. We did not find significant associations between any trajectory and cancer.Conclusions Trajectories related to stable and increasing depressive symptoms, but not the trajectory associated with severe depressive symptoms at the initial assessment but decreasing at the follow-up, were associated with higher risks of CVD and mortality. Alleviating severe depressive symptoms at the initial onset may mitigate CVD and mortality risks.